(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Thailand is undergoing nutritional transition from replacement of underweight to high prevalence of overweight and obesity in children. Family environment play critical role for successful prevention in childhood obesity. This study aims to determine factors contributing to awareness about childhood obesity among the parents and guardians of preschool children in an urban area of Nakon Prathom province, Thailand. A cross-sectional survey was conducted among 588 parents or guardians of preschool children at levels 1 and 2 of a kindergarten school. Data were collected using a self-administered questionnaire. Logistic regression was used to analyze related factors and covariates influencing parental awareness. A total of 495 (84.2%) completed questionnaires. Parental awareness was significantly associated to their education level and their beliefs regarding various approaches to combating childhood obesity. A number of demographic variables (age, household monthly income, family caregiver) had no statistically significant associations with parental awareness. The study indicated that incorrect beliefs increased the risk of low parental awareness about childhood obesity. Health education should be provided to increase knowledge of parents and guardians about ways of dealing with the problems of obesity and to help them to maintain healthy weights in their children.